ANALISIS NUMERIK DISTRIBUSI TEKANAN & KECEPATAN ALIRAN UDARA PADA FUSELAGE B737-9 MAX - Susilo, Tri; Rabeta, Bismil; Falah, Fikry (JTK: JURNAL TEKNOLOGI KEDIRGANTARAAN, 2019)
Aerodynamic characteristics can be known by using computational Fluid Dynamics (CFD) methods. This study analyzes the pressure distribution and velocity of air flow on Fuselage B737-9 MAX using the Computational Fluid Dynamics (CFD) method with variations in attack angles of 0o, 15o, 30o and 45o. The results obtained are at 0o attack angle, 15o the difference in speed and pressure is not too significant or normal, while at the attack angle 30o and 45o the difference in speed and pressure is very significant or abnormal because the air flow at that angle experiences turbulence around the fuselage.